Evaluating the regulatory alignment between special economic zones and governmental beneficiation objectives in South Africa - Rantlo, Tiisetso John (University of Pretoria, 2025)
Mini Dissertation (LLM (Extractive Industry Law in Africa))--University of Pretoria, 2024.